Extraction of Least-Dispersive Ultrasonic Guided Wave Mode in Rail Track Based on Floquet-Bloch Theory - Maodan Yuan; Peter W. Tse; Weiming Xuan; Wenjin Xu (Shock and Vibration)
Ultrasonic guided wave (UGW) has shown great potential in the field of structural health monitoring of rail tracks due to its long-range capability and full cross section coverage. However, the practical application of UGW has been hindered by the complicated signal interpretation because of the natures of multiple modes and dispersion. Therefore, it is desirable that the effective UGW modes with high excitability and least dispersion can be identified and extracted for practical applications. In this paper, a numerical study on the guided wave propagation was carried out on a standard rail with 56E1 profile. Firstly, Floquet-Bloch theory was applied to obtain the dispersion curves of guided wave in a rail. Then, a 3D FE model was built to investigate the UGW propagation along the rail within the frequency range of 0–120 kHz. Wavenumber-frequency analysis method was applied to decompose and identify the propagating UGW modes. With a carefully designed 2D bandpass filter, a specific mode W0 was extracted in the wavenumber-frequency domain. Finally, a frequency band sweep technique was also proposed to get the optimal frequency band to achieve a pure and least-dispersive UGW mode along the rail web. The proposed method provides an effective way to extract efficient UGW modes to assess the integrity of the rail track, as well as other waveguides with complex geometry.